MONETARY UNION IN AFRICA: WHO GAINS, LOSES, AND WHY? - Aladejebi, Babatunde Emmanuel; Mojekwu Ogechukwu Rita; Barisua Fortune Nwinee (Journal Park Publishing, 2025)
This research investigated the advantages and detractors of implementing a common currency in Africa, analysing critical elements like economic convergence, political and institutional readiness, and regional commercial integration. The results indicated that high-performing countries, like South Africa and Nigeria, would likely get the most advantages from a monetary union due to their varied markets, stable political systems, and robust institutional frameworks. In contrast, weak economies heavily dependent on natural resources, like Angola and Chad, may find it challenging to sustain stability under a common currency system, owing to their susceptibility to external economic shocks and insufficient diversification. Moreover, nations with deficient governance frameworks or those susceptible to political instability may have substantial obstacles in complying with the collective policies necessary for a successful monetary union. The study highlighted the significance of economic convergence, institutional capacity, and political cohesiveness for the success of the union, drawing on worldwide experiences from previous monetary unions, such the European Monetary Union (EMU) and the West African Economic and Monetary Union (WAEMU). The research determines that the advantages of a monetary union will be inequitably allocated, with some nations benefiting more than others owing to their varying degrees of economic growth and institutional preparedness. Based on these results, the research advocates for the formulation of explicit economic convergence criteria, the encouragement of economic diversification in resource-dependent nations, and the building of robust political and institutional frameworks to facilitate regional integration. A progressive approach to integration, including incremental economic coordination and policy alignment, is recommended to avoid possible dangers and assure the long-term viability of a single currency throughout Africa.
Keywords: Integration, Regional, Financial, Trade, Shocks.